Pendekatan Shrinking Core Model (SCM) Pada Reaksi Deasetilasi Kitin Menjadi Kitosan Dari Limbah Cangkang Kepiting - S, Muhammad Rizki; Drastinawati, Drastinawati; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Chitosan is a derivative of chitin compounds used in the biomedical field. The purpose of this research was to determine the effect of mixing speed on the degree of deacetylation of chitosan produced and can describe the reaction kinetics model with the Shrinking Core Model (SCM) approached. The procedure of research begins with the preparation of crab shells. Then crab shells were deproteinated with 3.5% NaOH, ratio 1:10 (b/v) for 2 hours and mixing speed by 150 rpm. After process of deproteinization, then demineralization with 1 N HCl, 1:15 (b / v) ratio for 1 hour and mixing speed of 150 rpm were carried out. The results of demineralization were chitin, then chitin was deacetylated with 55% NaOH, ratio 1:20 (b / v) at 120°C by varying the mixing speed by 100 rpm, 150 rpm and 200 rpm for 3 hours. Samples were taken every 15 minutes and increments of 10 mL, washed to neutral pH and dried. The degree of deacetylation of chitosan was analyzed by using the acid base titration method. The results showed that mixing speed was increased, the degree of deacetylation of chitosan also increased, each variation was 68,38%; 82,92% and 85,62%. The reaction kinetics model that was suitable for describing events that occur in chitosan synthesis were model 1, called diffusion through liquid film control. Keywords: crab shell, chitosan, degree of deacetylation, shrinking core model